Negative neurodynamic tests do not exclude neural dysfunction in patients with entrapment neuropathies. - Baselgia, L; Bennett, D; Silbiger, R; Schmid, A (Elsevier, 2016)
Objective To examine differences in somatosensory phenotypes of patients with positive and negative neurodynamic tests and compare these with healthy participants. Design Case-control study. Setting University department. Participants Patients with electrodiagnostically confirmed carpal tunnel syndrome (CTS) (nZ53) and people without CTS (nZ26) participated in this study (NZ79). Patients with CTS were subgrouped according to the results of the upper limb neurodynamic tests biasing the median nerve into patients with positive or negative neurodynamic tests. Main Outcome Measure All participants underwent quantitative sensory testing in the median innervated territory of their hand. Results Only 46% of patients with CTS had positive neurodynamic tests. No differences were identified between groups for pain thresholds (P>.247). However, patients with CTS had increased mechanical (P<.0001) and thermal detection thresholds (P<.0001) compared with people without CTS. Patients with negative neurodynamic tests had a more pronounced vibration detection deficit (mean, 7.43 ± 0.59) than people without CTS (mean, 7.89 ± 0.22;PZ.001). Interestingly, warm detection was the only domain differentiating positive (mean, 4.03°C ± 2.18°C) and negative neurodynamic test groups (6.09°C ± 3.70°C,PZ.032), with patients with negative neurodynamic tests demonstrating increased loss of function. Conclusions Patients with negative neurodynamic tests seem to have a more severe dysfunction of the unmyelinated fiber population. Our findings suggest that neurodynamic tests should not be used in isolation to judge neural involvement. Rather, they should be interpreted in the context of loss of function tests of the small fiber domain.